Identification of Multicolor Fluorescent Probes for Heterogeneous Aβ Deposits in Alzheimer’s Disease - Mukherjee, Abhisek; Al-Lahham, Rabab; Corkins, Mark E.; Samanta, Sourav; Schmeichel, Ann M.; Singer, Wolfgang; Low, Phillip A.; Govindaraju, Thimmaiah; Soto, Claudio (Frontiers in Aging Neuroscience, 2022)
Accumulation of amyloid-beta (A) into amyloid plaques and hyperphosphorylated tau into neurofibrillary tangles are pathological hallmarks of Alzheimer’s disease (AD). There is a significant intra- and inter-individual variability in the morphology and conformation of Aβ aggregates, which may account in part for the extensive clinical and pathophysiological heterogeneity observed in AD. In this study, we sought to identify an array of fluorescent dyes to specifically probe Aβ aggregates, in an effort to address their diversity. We screened a small library of fluorescent probes and identified three benzothiazole-coumarin derivatives that stained both vascular and parenchymal Aβ deposits in AD brain sections. The set of these three dyes allowed the visualization of Aβ deposits in three different colors (blue, green and far-red). Importantly, two of these dyes specifically stained Aβ deposits with no apparent staining of hyperphosphorylated tau or α-synuclein deposits. Furthermore, this set of dyes demonstrated differential interactions with distinct types of Aβ deposits present in the same subject. Aβ aggregate-specific dyes identified in this study have the potential to be further developed into Aβ imaging probes for the diagnosis of AD. In addition, the far-red dye we identified in this study may serve as an imaging probe for small animal imaging of Aβ pathology. Finally, these dyes in combination may help us advance our understanding of the relation between the various Aβ deposits and the clinical diversity observed in AD.